2021
DOI: 10.1001/jamanetworkopen.2021.21758
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cobalturia Among Adults With Joint Replacements

Abstract: Twenty million North Americans have cobalt-chrome arthroprosthetic components, and 1 million have metal-on-metal hip replacements. 1 Cobalt is a mitochondrial toxin-encephalopathy and cardiomyopathy (cobaltism) may occur from iatrogenic, industrial, dietary, or arthroprosthetic cobalt exposure. 2,3 In unexposed populations, the 95th percentile of cobalt levels in urine and blood are 1 part per billion (ppb) and 0.4 ppb, respectively. 3 Wear and corrosion of cobalt-chrome joint implantations can result in perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 6 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…The surgeon-author or a local colleague performed 179 (78%) of the at-risk arthroplasties. Table 3 lists the location, type, location, brand and model of the various cobalt-chromium components and the risk-level of their implantation to result in cobalturia as categorized in another publication studying the same patient cohort [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The surgeon-author or a local colleague performed 179 (78%) of the at-risk arthroplasties. Table 3 lists the location, type, location, brand and model of the various cobalt-chromium components and the risk-level of their implantation to result in cobalturia as categorized in another publication studying the same patient cohort [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the American National Health and Nutrition Examination Survey (NHANES) database of 3442 adults found subjects with a blood-cobalt of >0.17 ppb (equivalent to urine-cobalt of 0.7 ppb) [ 4 ], have increased prevalence of cardiovascular disease compared to those with a blood-cobalt ≤0.11 ppb [ 41 ]. Another NHANES study of 947 women found a significantly higher prevalence of metabolic-syndrome in subjects with urine-cobalt of ≥0.95 ppb compared to those with urine-cobalt ≤0.38 ppb [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations